Uksztaltowanie kregoslupa u mlodziezy trenujacej plywanie - Fajdasz, A.; Zaton, K. (Medycyna sportowa, 2000)
The effects of physical activity in aqueous environment on a harmonious development of human beings have been widely acknowledged. A prolonged activity of that kind, e.g. swimming training, may, however, induce or deepen postural abnormalities, especially in the thoracic region. The aim of this study was thus to find out whether a long-lasting training in swimming might be a factor in developing spinal disorders. Material and methods: A group of 32 adolescents aged 14-15 years, having training history of 4-5 years, were studied. It was assumed that such a training period would be sufficient to produce possible effects on the spine. An age-matched control group consisting of untrained subjects was also selected. The Moirey's computer-aided procedure was applied to assess the posture and Excel functions were used to process the results. Conclusions: Young swimmers differed in their body posture from the untrained controls; Swimmers displayed a predominantly kyphotic posture and their bodies in an upright position were inclined forward; The swimmers displayed a nearly ideal spinal line in the frontal plane, the asymmetry of shoulders, shoulder-blades and waist being negligible in contrast to control subjects.